Pengaruh Model Pembelajaran Kooperatif Tipe STAD Terhadap Hasil Belajar Matematika Siswa di SMP Negeri 1 Tutuyan - Sarah Alheid; Victor R. Sulangi; Sylvia J. A. Sumarauw (Departement of Mathematics Education, 2024)
This research aims to find out whether the mathematics learning outcomes of students taught using the STAD cooperative learning model are higher than the mathematics learning outcomes of students using the lecture method. This research is quasi-experimental in the form of the nonequivalent posttest-only control group design. The subjects in this research were class VIII students at SMP Negeri 1 Tutuyan odd semester of the 2022/2023 academic year, where VIII-A, totaling 20 students, was the experimental class and VIII-B, totaling 21 students, was the control class. Data analysis used includes normality tests, homogeneity tests, and hypothesis tests. This research uses a test in the form of multiple choice questions and a description of relationship and function material as the instrument. The research participants consisted of 41 students. Based on hypothesis testing using the t-test statistic, tcount = 2.365 and ttable = 1.685 at a significance level of 0.05. Thus, because tcount > ttable, H0 is rejected. The results of the research concluded that student learning outcomes in the Relationships and Functions material taught using the STAD model were higher than student learning outcomes taught using the lecture method.